Single‐Cell Mechanical Characterization of Human Macrophages. Issue 7 (28th April 2022) - Evers, Tom M. J.; Sheikhhassani, Vahid; Tang, Huaqi; Haks, Mariëlle C.; Ottenhoff, Tom H. M.; Mashaghi, Alireza
Abstract : Macrophages remodel their mechanics during differentiation toward different subtypes and drastically adapt their shapes during phagocytosis or entry to inflamed tissues. Although these functions depend on cell mechanical properties, the mechanical behavior of macrophages is still poorly understood and accurate physiologically relevant data on basic mechanical properties of different macrophage subtypes are lacking almost entirely. By combining several complementary single‐cell force spectroscopy techniques, whole cell mechanics of M1 (differentiated by granulocyte macrophage colony‐stimulating factor [GM‐CSF]) and M2 (differentiated by macrophage colony‐stimulating factor [M‐CSF]) macrophages is systematically analyzed, and it is revealed that M2 macrophages exhibit solid‐like behavior, whereas M1 macrophages behave more fluid‐like. In addition, the findings indicate that M2 macrophages exhibit increased dynamic motility as compared to M1 macrophages, consistent with their mechanical phenotypes. The technology presented herein can be used to distinguish macrophage subtypes based on their mechanical phenotype, and suggests that mechanical properties of macrophages are linked to their immune function. Abstract : Mechanical properties of M1 and M2 macrophages relate to the key physiological functions of these cells. Herein, it is demonstrated that M2 macrophages are stiffer than M1 macrophages, and that M2 macrophages exhibit stronger migratory ability as compared to M1 macrophages. These differences in macrophage mechanical phenotype and function may help provide novel biomarkers of immune activation and disease.